Why do growth rates differ? Evidence from cross-country data on private sector production - Juha Kilponen; Matti Virén (Bank of Finland, 2008)
We estimate a standard production function with a new cross-country data set on business sector production, wages and R&D investment for a selection of 14 OECD countries including the United States. The data sample covers the years 1960-2004. The data suggest that growth differences can largely be explained by capital deepening and an ability to produce new technology in the form of new patents. The importance of patents is magnified by the openness of the economy. We find some evidence of increasing elasticity of substitution over time, all though the results are sensitive to assumptions on the nature of technological progress.
URN:NBN:fi:bof-20140807679
Keywords: O40; E10; O43; 330; growth; R&D; production function; patents